KONSEP MUTU DAN TOTAL QUALITY MANAJEMENT (TQM) DALAM DUNIA PENDIDIKAN - Asmuni Asmuni (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2013)
Recently, educational world is so striking because the government has been been doing and focusing on some efforts to build the concept of educational quality. One of the steps is a curriculum renewal in 2013. Although the 2013 curriculum has similar substance as the previous curriculum, one difference only lies on the method, namely Thematic Method. However, the curricullum cannot be separated from the quality of education itself that needs to be considered carefully, and great confidence arises when a new policy with extraordinary vision to 2025 that is to establish “smart and competitive Indonesian pupil (Perfect/ generous human being)